Využití obnovitelných zdrojů v ČR - Kopička, Marek (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2010)
Tato práce se zabývá úvahou nad skladbou energetických zařízení v ČR. Je zde popsán jejich vývoj z hlediska: spotřeby elektrické energie, skladby energetických zařízení a cen za elektřinu. Dále je zde popsána struktura výroby elektrické energie k roku 2009 z hlediska: výroby, zdrojů, spotřeby a poměru výroben. Je zde samozřejmě zmíněn vliv a podíl OZE na poli tohoto vývoje a struktury. Další část práce je zaměřena na základní popis jednotlivých zdrojů elektrické energie. Zmíněny jsou nejen výrobny využívající pro svou výrobu elektrické energie obnovitelných primárních zdrojů, ale i ostatní typy výroben. Shrnuty jsou jejich výhody a nevýhody. Poslední částí této práce je úvaha nad realizací fiktivního projektu, který by mohl nahradit část podílu parních elektráren na výrobě elektrické energie obnovitelnými zdroji. Jsou zde propočteny a navrhnuty různé možnosti realizace z hlediska potřebného instalovaného výkonu a přibližného odhadu investičních nákladů.

This thesis deals with consideration of energy facilities structure in Czech Republic. It is depicted in it their evolution from point of: electric energy consumption, structures of energy facilities and electricity prices. Further, is here depicted a production of electric energy for the year 2009, from the point of: produce, sources, consumption and ratio of factories. Of course, the RSE (renewable sources of energy) effect and share of scope on this evolution and structure, is also mentioned here. The next part is pointed to basic description of each sources of electric energy. It is not mentioned here only factories which uses for it´s production renewable primary sources but also another types of factories. Their pros and cons are also summarized. The last part of this work is a thought of realization of fictive project, which could replace a part of steam power plants' share by producing electric energy through renewable sources. It is re-counted and suggested here a few possibilities of this realization from the point of needed installed power and approximate estimation of capital expenditure.
Utilization of renewable energy sources in Czech Republic
Keywords: Obnovitelné zdroje energie; vodní energie; větrná energie; sluneční energie; geotermální energie; energie biomasy; denní diagram spotřeby; roční diagram spotřeby; koeficient ročního využití.; Renewable energy sources; water energy; wind energy; solar energy; geothermal energy; biomass energy; daily consumption diagram; yearly consumption diagram; coefficient of year's utilization.